Kinetics-controlled synthesis of gold–silver nanosheets with abundant in-plane cracking and their trimetallic derivatives for plasmon-enhanced catalysis. Issue 13 (9th March 2022) - Zheng, Yiqun; Zhang, Gongguo; Ma, Yanyun; Kong, Yuhan; Liu, Feng; Liu, Maochang
Abstract : Branched AuAg-based multimetallic nanosheets are successfully prepared via sequential synthesis, exhibiting noticeable plasmon-enhanced catalytic activity under UV-vis light irradiation. Abstract : Controlled synthesis of two-dimensional noble metal nanomaterials with an in-plane branching morphology has been of great research interest recently, but has so far achieved limited success for AuAg-based nanocrystals. Herein, we report the fabrication of gold–silver (AuAg) nanosheets with abundant in-plane cracking and sub-10 nm thickness via one-pot kinetics-controlled synthesis. In particular, the dropwise addition of Au/Ag precursor solutions into a mixture of octadecyltrimethylammonium chloride and ascorbic acid, kept in an ice–water bath, leads to the formation of nanobelts/nanowires initially, followed by their growth into branched nanosheets. These AuAg products can further convert to AuAgM (M = Pd or Pt) nanosheets via galvanic replacement reaction under ambient conditions. Interestingly, the AuAgPd nanosheets are obtained with a Au@PdAg core–shell elemental distribution with many zigzag edges. In contrast, the AuAgPt nanosheets show a homogeneous distribution of all three metals, together with a highly stippled surface. All these AuAg-based nanosheets exhibit strong absorbance in the near-infrared region and thus show superb activities as photocatalysts for UV-vis light-assisted reduction of 4-nitrophenol due to the effect of plasmon enhancement. The present study provides a feasible route to generating AuAg-based multimetallic nanocrystals with a two-dimensional structure, in-plane branching morphology, and effective control over the elemental distribution, which could be potentially extended to other noble metals and/or alloys for the rational design of plasmonic photocatalysts.